2018
DOI: 10.1002/14651858.cd009447.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation for perioperative thromboprophylaxis in people with cancer

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 127 publications
1
30
0
Order By: Relevance
“…However, we observed no difference between groups with regard to serious bleeding events (LMWH 12.5% vs UFH 22.7%, P = .31). This mirrors the results of recent publications on the use of enoxaparin, including a Cochrane review on its perioperative use, showing a reduction of bleeding rates . Reduced bleeding rates add to a number of other well described benefits with the use of LMWH, such as reduced rates of heparin‐induced thrombocytopenia, reduced activation of thrombocytes and improved bioavailability, ease of administration as well as reduced need for laboratory monitoring …”
Section: Discussionsupporting
confidence: 73%
“…However, we observed no difference between groups with regard to serious bleeding events (LMWH 12.5% vs UFH 22.7%, P = .31). This mirrors the results of recent publications on the use of enoxaparin, including a Cochrane review on its perioperative use, showing a reduction of bleeding rates . Reduced bleeding rates add to a number of other well described benefits with the use of LMWH, such as reduced rates of heparin‐induced thrombocytopenia, reduced activation of thrombocytes and improved bioavailability, ease of administration as well as reduced need for laboratory monitoring …”
Section: Discussionsupporting
confidence: 73%
“…Prognostic factors for NLDVT were CVC presence and acute infection. The first finding is not surprising, given that CVCs are a well-known risk factor for thrombosis [ 2 , 33 ]. The latter is a new finding that needs confirmation in a follow-up study.…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized studies and meta-analysis have demonstrated the benefit of pharmacologic prophylaxis with LMWH and UFH over no prophylaxis or placebo unless there is a contraindication [9].…”
Section: Prophylaxis Of Vte In Surgical Cancer Patientsmentioning
confidence: 99%